Design and synthesis of luminescent porous coordination polymers for chromaticity modulation, sensing of nitrobenzene and iodine encapsulation. Issue 30 (20th June 2016) - Wang, Haijun; Cheng, Fujun; Zou, Changchang; Li, Qianqian; Hua, Yinying; Duan, Jingui; Jin, Wanqin
Abstract : A family of porous coordination polymers constructed from C 2v symmetry ligands with increased conjugation moieties was systematically designed and prepared, which is highly promising for chromaticity modulation, sensing of nitrobenzene, and I2 encapsulation. Abstract : We design and prepare a family of luminescent porous coordination polymers (PCPs) constructed from three C 2v symmetry ligands with increased conjugation moieties. Single crystal X-ray analyses revealed that their pore types/sizes and volumes were systematically tuned. Eu-based NTU-5 and NTU-8 emit red light. However, in contrast to the typical green emission of Tb-based PCPs, the increased conjugation moieties in NTU-6 and NTU-9 with a Tb center resulted in a very unusual blue emission. These unique emissions from these iso-structures demonstrated varied pathways of electronic transfer, which were further confirmed by lifetime experiments. Encouraged by these observations, the chromaticity modulation from pink to blue has been well realized by a facile method of self-assembly of the Te-H3 L ligand and varied molar ratios of Eu 3+ /Tb 3+ ions. Additionally, NTU-6 and NTU-9 showed high potential for nitrobenzene sensing (quenching effect coefficients: 589.5 and 445.6 M −1 ) and encapsulation of I2 molecules.